PROGRESO-II: Developing Culturally Tailored Materials for a Social Network-Based Intervention to Promote HIV Pre-Exposure Prophylaxis Initiation Among Latina Seasonal Farmworkers. - Rodriguez, Edda; Boga, Devina J.; Shrader, Cho Hee; Arroyo-Flores, Juan; Rosas, Yesenia; Kanamori, Mariano (AIDS Patient Care & STDs, 2024)
Latina Seasonal Farmworkers (LSFW) in South Florida are a community affected by human immunodeficiency virus (HIV) due to cultural barriers, stigma, and lack of awareness of pre-exposure prophylaxis (PrEP). Building on the PROGRESO study, this study sought to: (1) develop and pre-test scientifically supported and culturally tailored PrEP materials for PROGRESO and (2) assess the acceptability of these PrEP materials by LSFW who use alcohol and/or drugs. PrEP messages were selected based on a literature review, feedback from experts working on PrEP programs, and recommendations from a four-member scientific expert panel through a two-level Delphi method. A culturally tailored PrEP presentation was developed and presented to sixteen LSFW, who engaged in four focus groups. Materials were modified based on participants' suggestions. Thematic analysis was used to assess the acceptability and usability of these materials in the LSFW community. Participants responded positively to the PrEP messages and understood their importance for Latinx communities. Participants felt empowered and comfortable enough with the information to distribute the messages to partners, children, and friends with the aid of a physical pamphlet or flyer. A strong cultural context of familialismo and confianza was present in comments made by our participants. This study has the potential to increase LSFW's PrEP awareness and initiation. Future studies may implement a hybrid-interview approach, allowing individuals to self-select into a virtual or in-person focus group. Such flexibility may increase participation and discussion by allowing participants to attend in a format they are most comfortable with, as noted by participants in this study.